2020
DOI: 10.1017/s000711452000478x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and their associations with the metabolic syndrome and predicted 10-year risk of CVD in northwest Chinese adults

Abstract: The diet impact on metabolic syndrome(MetS) and cardiovascular diseases has been investigated widely, but few studies investigated the association between dietary patterns(DPs) and the the predicted cardiovascular disease, derived from reduced-rank regression (RRR). The objectives of this study were to derive DPs using RRR and principal component analysis (PCA), and investigate their associations with MetS and estimated 10-year atherosclerotic cardiovascular disease (ASCVD). We used the baseline dataset from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…PCA was used to develop a formula to calculate a metabolic syndrome severity score, which was shown to be useful in the assessment of cardiometabolic risk factors [ 72 ]. A number of papers on the importance of dietary patterns that were identified using PCA in the context of MS have also been published [ 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCA was used to develop a formula to calculate a metabolic syndrome severity score, which was shown to be useful in the assessment of cardiometabolic risk factors [ 72 ]. A number of papers on the importance of dietary patterns that were identified using PCA in the context of MS have also been published [ 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intensively trained interviewers assessed the habitual diet of participants using a semiquantitative food frequency questionnaire (FFQ), which has been presented previously [ 27 ]. The FFQ included 127 food items and was used to assess the frequency (daily, 4∼6 times/week, 1∼3 times/week, 1∼3 times/month, and never or rarely) and quantity of consumption (in units or specified portion size) for the past year.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, this was a population-based study organized from April 2018 to May 2019. e ethical clearance for this study came from the Xinjiang Uyghur Autonomous Region Institute of Traditional Chinese Medicine (2018XE0108), and all patients signed written informed consent certificates. More details of the XMEC have been reported elsewhere [27].…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Moreover, few studies internationally have been undertaken that were specific to the higher risk, older population. Studies have been conducted with adults older than 50 years (China, n 1006) (28) and populations with a mean age greater than 60 years (10,29,30) . These studies reported inverse associations between dietary patterns with healthy food groups and the metabolic syndrome.…”
mentioning
confidence: 99%
“…These studies reported inverse associations between dietary patterns with healthy food groups and the metabolic syndrome. For example, a pattern containing red dates, gouji berries, dried fruit, nuts and grains in a Chinese population (Urumqi cohort, n 4265) was protective (29) , as was one high in fruit and vegetables and low in red and processed meats in a German cohort (n 853) (30) . In contrast, the metabolic syndrome was positively associated with dietary patterns containing milk tea but not yogurt in the Urumqi cohort (29) ; legumes, beef, processed meat and bouillon in a German population (n 905) (10) ; and a 'Western' cluster (n 343) compared with a 'healthy' cluster (n 353) in an older Chinese population (28) .…”
mentioning
confidence: 99%